Psychological and hormonal indicators of stress (serum cortisol and prolactin) in mothers of preterm newborns admitted to a neonatal intensive care unit - Torrecilla, Norma Mariana (2025)
Objective: To evaluate variations in psychological stress, as well as cortisol and prolactin (PRL) levels, in mothers of preterm newborns (NBs) by examining the changes between the initial days of their child’s admission to a neonatal intensive care unit (NICU) and the time prior to hospital discharge. Materials and methods: A quantitative study using a non-experimental, cross-sectional, descriptive survey design with a comparative approach. The sample consisted of 35 mothers of preterm NBs, selected through purposive sampling. The inclusion criteria required that infants be hospitalized in an NICU due to prematurity (< 1500 g birth weight and < 32 weeks of gestation) and that mothers attend the breastfeeding center (BC) to express milk to support breastfeeding. Mothers with a history of psychiatric disorders, as reported during pre-study interviews, were excluded. Results: Markedly higher levels of psychological stress were observed upon admission to the NICU in relation to aspects and sounds of the unit, the infant’s appearance and behavior, the mother-child relationship and the parent’s role. These stress levels decreased prior to hospital discharge. No significant differences were found in communication with the healthcare team. Cortisol levels notably increased between the two time points, peaking prior to discharge. No significant differences were observed in prolactin levels. Conclusions: Psychological stress decreases as discharge approaches, whereas cortisol levels increase, indicating a persistent physiological response. Monitoring stress levels over time is essential for identifying critical moments. Simultaneous assessment of psychological stress and hormone levels provides a more comprehensive follow-up of maternal progress and the effectiveness of interventions, facilitating timely adjustments in support and treatment strategies.